21 Psychedelic treatment of functional neurological disorder – a systematic review. Issue 8 (20th July 2020) - Butler, Matthew; Seynaeve, Mathieu; Nicholson, Timothy R; Pick, Susannah; Kanaan, Richard A; Lees, Andrew; Young, Allan H; Rucker, James
Abstract : Aims: Functional neurological disorder (FND), formerly known as conversion disorder, causes a high burden of disability and distress, and is amongst the most commonly encountered conditions in neurology clinics and neuropsychiatry services, yet the therapeutic evidence base is limited. Research into psychedelics such as psilocybin and lysergic acid diethylamide (LSD) is currently being undertaken with significant renewed interest, and in recent studies psychedelics have shown promise in treating a range of psychiatric conditions. Modification of neural circuits associated with self-representation is thought to underlie some of this effect, and as some contemporary theories of FND focus on aberrant somatic self-representation, psychedelics may therefore represent an unexplored treatment option for FND. METHODS: We systematically reviewed studies involving the use of psychedelics in FND. Nine studies published between 1954 – 1967, with a total of 26 patients, were identified. Due to restriction of licencing of psychedelic drugs since this period, no modern studies were identified. Results: LSD was the most commonly used psychedelic, with some studies also using psilocybin and/or mescaline. The number of therapeutic sessions of psychotherapy ± psychedelic substance administration ranged from one to 26, with descriptions of therapeutic methods used widely varying, and in some cases not described in any detail. Psychedelics were given either orally or intramuscularly, with doses of LSD ranging from 25 to 2, 000 micrograms (mcg), and doses of psilocybin ranging from 3 to 15 milligrams (mg). Of those treated, 69% (n=18) were found to have made at least some recovery, with 23% (n=6) having completely recovered after psychedelic therapy. Adverse events were typically mild and transient. Conclusions: Studies were generally of low quality, often lacking control groups and valid outcome measures. Despite this, the degree of improvement is considerable, even if the presumptive bias in favour of the treatment in the studies is taken into consideration. Furthermore, good therapeutic outcomes and lack of adverse events in modern open-label trials utilising psychedelic therapy for neuropsychiatric disorders is encouraging. Advances in the understanding of the neurobiology of FND, as well as further modern clinical research into the therapeutic utility of psychedelics, may help to determine whether psychedelics offer a feasible, safe and effective treatment for FND.